Filamentous Fungus Aspergillus oryzae for Food: From Submerged Cultivation to Fungal Burgers and Their Sensory Evaluation—A Pilot Study - Neda Rousta; Coralie Hellwig; Steven Wainaina; Lukitawesa Lukitawesa; Swarnima Agnihotri; Kamran Rousta; Mohammad J. Taherzadeh (Foods, 2021)
New food sources are explored to provide food security in sustainable ways. The submerged fermentation of edible filamentous fungi is a promising strategy to provide nutritious and affordable food that is expected to have a low environmental impact. The aim of the current study was to assess the novel use of Aspergillus oryzae cultivated in submerged fermentation on oat flour as a source for food products that do not undergo secondary fermentation or significant downstream processing. The fungus was cultivated in a pilot-scale airlift bioreactor, and the biomass concentration and protein content of the biomass were assessed. A tasting with an untrained panel assessed consumer preferences regarding the taste and texture of minimally processed vegetarian and vegan burger patties made from the biomass, and how the patties fared against established meat-alternative-based patties. The cultivation of Aspergillus oryzae resulted in a yield of 6 g/L dry biomass with a protein content of 37% on a dry weight basis. The taste and texture of the minimally processed fungal burger patties were to the liking of some participants. This was also reflected in diverse feedback provided by the participants. The cultivation of the fungus on oat flour and its utilization in developing burger patties shows its promising potential for the production of nutritious food. The applications of the fungus can be further developed by exploring other favorable ways to texture and season this relatively new functional food source to the preferences of consumers.